Exosomes and Obesity-Related Insulin Resistance - Lei, Li-Min; Lin, Xiao; Xu, Feng; Shan, Su-Kang; Guo, Bei; Li, Fu-Xing-Zi; Zheng, Ming-Hui; Wang, Yi; Xu, Qiu-Shuang; Yuan, Ling-Qing (Frontiers in Cell and Developmental Biology, 2021)
Exosomes are extracellular vesicles, delivering signal molecules from donor cells to recipient cells. The cargo of exosomes, including proteins, DNA and RNA, could target the recipient tissues and organs, which have an important role in disease development. Insulin resistance is a kind of pathological state, which is important in the pathogeneses of type 2 diabetes mellitus, gestational diabetes mellitus and Alzheimer’s disease. Furthermore, obesity is a kind of inducement of insulin resistance. In this review, we summarized recent research advances on exosomes and insulin resistance, especially focusing on obesity-related insulin resistance. These studies suggest that exosomes have great importance in the development of insulin resistance in obesity and have great potential for use in the diagnosis and therapy of insulin resistance.